2021
DOI: 10.1111/aas.13835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on evoked‐potential monitoring in patients undergoing brain stem and supratentorial cranial surgery

Abstract: Background Dexmedetomidine is used as adjuvant in total intravenous anaesthesia (TIVA), but there have been few studies concerning its effect on intraoperative neurophysiological monitoring (IONM) during cranial surgery. Our aim was to study the effect of dexmedetomidine on IONM in patients undergoing brain stem and supratentorial cranial surgery. Methods Two prospective, randomized, double‐blind substudies were conducted. In substudy 1, during TIVA with an infusion of propofol and remifentanil, 10 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
2
5
1
Order By: Relevance
“…Lee et al [ 36 ] in their study observed that the baseline amplitude was lower in the dexmedetomidine group and required higher stimulation currents for achieving the baseline values. Similar requirements of higher stimulation intensities were also observed in the study by Pacreu et al [ 35 ] in cranial surgeries without significantly affecting the amplitude and latency of SSEPs and MEPs. These did not hinder the correct interpretation of the responses throughout the surgery.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Lee et al [ 36 ] in their study observed that the baseline amplitude was lower in the dexmedetomidine group and required higher stimulation currents for achieving the baseline values. Similar requirements of higher stimulation intensities were also observed in the study by Pacreu et al [ 35 ] in cranial surgeries without significantly affecting the amplitude and latency of SSEPs and MEPs. These did not hinder the correct interpretation of the responses throughout the surgery.…”
Section: Discussionsupporting
confidence: 85%
“…The mean propofol consumption was lower in the dexmedetomidine group (101.4 ± 13.5 µg/kg/min) when compared to the fentanyl group (148 ± 29.8 µg/kg/min) by approximately 30% and was statistically significant (p < 0.001) (Table 2). Our finding was at par with other studies, demonstrating a propofol-sparing effect of dexmedetomidine due to its α-2 agonist activity on the locus ceruleus [12][13][14][15]19,28,29,[30][31][32][33][34][35][36][37][38][39]. Chakrabarti et al [33] reported similar findings in patients undergoing cerebellopontine angle surgeries with TIVA when dexmedetomidine was used as an adjuvant.…”
Section: Mean Propofol Consumptionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a retrospective case-controlled study of 70 pediatric patients undergoing posterior spine surgery, dexmedetomidine infusion at 0.3 to 0.5 mcg/kg/h without bolus was associated with a statistically and clinically significant reduction in TcMEP amplitude from baseline. 22 In a prospective, double-blinded RCT by Pacreu et al, 23 40 patients undergoing intracranial tumor resections were randomized to receive either dexmedetomidine 0.5 mcg/kg/h infusion without bolus or normal saline infusion, in addition to propofol and remifentanil infusions for anesthesia maintenance; 23 TcMEP stimulation threshold was significantly higher in the dexmedetomidine group, though the TcMEP and SSEP amplitudes were not different between the 2 groups. In a double-blinded RCT involving 160 patients undergoing thoracic spine surgery, participants were randomized to receive either dexmedetomidine 1 mcg/kg bolus followed by 0.5 mcg/kg/h infusion, dexmedetomidine 0.5 mcg/kg/h infusion without bolus, or placebo infusion.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…As a result, spinal surgery benefits from combined intravenous inhalation anesthesia. As an adjuvant, dexmedetomidine (Dex) may be useful in reducing the need for propofol [ 9 , 10 ]. For example, the induction dose of propofol can be reduced by 15% and the demand for propofol can be reduced by 29% by adding Dex to TIVA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%